Potensi Pembelajaran Aktif dengan Metode Kontruktivisme - Asrinawati Asrinawati; Evifa Luthfiah Sya’bani Choirunisa; Nadia Nur Khamilah Al-Hafidz; Sekar Ayu Pamela; Fitria Pusparini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The aim of this research is to evaluate how effective the constructivism approach is in increasing student activity and their learning outcomes using meta-analysis methods. The data used comes from previous literature research, which includes articles and academic journals related to constructivist learning. Inclusion criteria include discussing constructivism theory directly, presenting data on improving learning outcomes from the pre-cycle, cycle I, and cycle II stages, and being published in 2020–2024. Articles that were not relevant to the topic, did not include quantitative data, or were not available in full were excluded from the analysis. Based on research results, the constructivist approach shows significant changes in increasing student academic achievement. The Pearson correlation test shows a strong relationship between pre-cycle and cycle II, and statistical analysis using the Paired Sample T-Test shows that there are significant differences at each learning stage. Apart from that, this method has been proven to increase student activity in learning. This study shows how important it is to use a constructivist approach to create active and meaningful learning. By using this approach, students can be helped to increase understanding and improve learning outcomes.